2005
DOI: 10.1073/pnas.0504097102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycosides inhibit TNF-α/NF-κB signaling by blocking recruitment of TNF receptor-associated death domain to the TNF receptor

Abstract: Digitoxin and structurally related cardiac glycoside drugs potently block activation of the TNF-␣͞NF-B signaling pathway. We have hypothesized that the mechanism might be discovered by searching systematically for selective inhibitory action through the entire pathway. We report that the common action of these drugs is to block the TNF-␣-dependent binding of TNF receptor 1 to TNF receptor-associated death domain. This drug action can be observed with native cells, such as HeLa, and reconstituted systems prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 35 publications
(42 reference statements)
5
66
0
Order By: Relevance
“…Other investigators have reported that cardiac glycoside drugs, such as digitoxin and oleandrin, inhibit the constitutive hypersecretion of nuclear factor κB-dependent proinflammatory cytokine interleukin 8 from cystic fibrosis lung epithelial cells (13). These investigators also observed that oleandrin, as well as digoxin, suppressed the tumor necrosis factor-α/nuclear factor κB signaling pathway by blocking tumor necrosis factor-α-dependent TNFR1/TRADD complex formation (14). Oleandrin has also been shown to induce apoptosis in human leukemia cells by dephosphorylation of Akt, expression of FasL, as well as alteration of membrane fluidity (9).…”
Section: Introductionsupporting
confidence: 48%
“…Other investigators have reported that cardiac glycoside drugs, such as digitoxin and oleandrin, inhibit the constitutive hypersecretion of nuclear factor κB-dependent proinflammatory cytokine interleukin 8 from cystic fibrosis lung epithelial cells (13). These investigators also observed that oleandrin, as well as digoxin, suppressed the tumor necrosis factor-α/nuclear factor κB signaling pathway by blocking tumor necrosis factor-α-dependent TNFR1/TRADD complex formation (14). Oleandrin has also been shown to induce apoptosis in human leukemia cells by dephosphorylation of Akt, expression of FasL, as well as alteration of membrane fluidity (9).…”
Section: Introductionsupporting
confidence: 48%
“…These other functions appear to be nonexclusive. For example, digitoxin blockade of proinf lammatory TNF-␣/NF-B signaling occurs at subnanomolar concentrations (17,18,28). This function is therefore unlikely to be dependent on digitoxin calcium channels, which only become active above a threshold of ca.…”
Section: Discussionmentioning
confidence: 99%
“…Non-NaKATPase effects also have been observed. For example, quite low subnanomolar concentrations of the cardiac glycoside digitoxin also are able to block TNF-␣/NF-B signaling (17,18). Thus, the mechanism for calcium-specific actions of digitoxin and other medicinal cardiac glycosides remains to be fully understood.…”
mentioning
confidence: 99%
“…Weaker edges connect two of the three tested compounds to community n. 63, consisting of Na þ ∕K þ -ATPase membrane pump inhibitors. This proximity might be explained by the fact that inhibition of Na þ ∕K þ -ATPases by cardiac glycosides has been shown to affect NF-kB signaling (31). Fuzzy GO term enrichment analysis showed that genes involved in the response to unfolded proteins are upregulated in community n. 28 and community n. 104, whereas community n. 40 is enriched for GO terms relative to endoplasmatic reticulum overload and stress.…”
mentioning
confidence: 97%